Relationship between self-medication for handling toothache and the socioeconomic- cultural level of residents of the district of Independence Huaraz 2007 - Aguedo Del Castillo, Annabell (2008)
The aim of the investigation was to determine the relationship between self-medication and the socioeconomic- cultural level for handling toothache, in Ancash, Peru: District of Independence, Province of Huaraz. The study was descriptive-correlational, cross-sectional and retrospective. It was interviewed 400 residents of different small villages from the district. The results verified the general hypothesis: It exists an inverse relationship between self-medication for handling toothache and the socioeconomiccultural level of residents, through the tests of correlation: V of cramer (v = 0.547) and Pearson (p = -987); also, the specific hypothesis: It exists a greater correlation between the self-medication and the cultural level (v = 0.527) than to social (v = 0.375) and economic (v = 0.362) levels, was proved. It was found that the prevalent attitude to relief a toot pain is the self-medication (72.75%) being the main type: the pharmacologic self-medication (64.61%), with AINES the type of medicine more frecuently used (49,25%); and the traditional auto medication type with Vegetal origin (15,50%). Residents minor to 30 years old (39,86%), and female gender (59,50%), were the groups that used auto medication more than the others. The pharmacist (36,80%) is the person who mainly advises of taking medicine, and the pharmacy (78,00%), the place where mainly the medicine is acquired. The effectiveness of the medicine is greater in the pharmacologic auto medication (54,00%) and the times of uses to relief tooth pain, is two. It was concluded that existed an inversely proportional correlation between the socioeconomiccultural level and the residents’ self-medication attitude on handling toothache.